Study of financial sustainability variables in agroecosystems for: Venezuela, Spain, Colombia, Peru and Cuba (Revista cientifica In Vestigium Ire, 2020)
Agricultural systems refer to those ecosystems that in one way or another have been manipulated by humans in relation to agricultural or livestock production, so it is important to assess their impact in terms of financial sustainability by analyzing economic indicators related to the consumption of capital, human, natural and production resources. In this sense, the objective of this article is to identify the variables that influence the financial sustainability of agro-ecosystems, highlighting their importance, contribution, and viability, as well as detailing the need for sustainable models for financial development and maintenance.
Keywords: Ecosystem; services; sustainability; agriculture